Synthesis and Psychotropic Properties of Novel Condensed Triazines for Drug Discovery - Ervand G. Paronikyan; Shushanik Sh. Dashyan; Suren S. Mamyan; Ruzanna G. Paronikyan; Ivetta M. Nazaryan; Kristine V. Balyan; Hrachik V. Gasparyan; Sona A. Buloyan; Lernik S. Hunanyan; Nina G. Hobosyan (MDPI AG, 2024)
The exploration of heterocyclic compounds and their fused analogs, featuring key pharmacophore fragments like pyridine, thiophene, pyrimidine, and triazine rings, is pivotal in medicinal chemistry. These compounds possess a wide array of biological activities, making them an intriguing area of study. The quest for new neurotropic drugs among derivatives of these heterocycles with pharmacophore groups remains a significant research challenge. The aim of this research work was to develop a synthesis method for new heterocyclic compounds, evaluate their neurotropic and neuroprotective activities, study histological changes, and perform docking analysis. Classical organic synthesis methods were used in the creation of novel heterocyclic systems containing pharmacophore rings. To evaluate the neurotropic activity of these synthesized compounds, a range of biological assays were employed. Docking analysis was conducted using various software packages and methodologies. The neuroprotective activity of compound 13 was tested in seizures with and without pentylenetetrazole (PTZ) administration. Histopathological examinations were performed in different experimental groups in the hippocampus and the entorhinal cortex. As a result of chemical reactions, 16 new, tetra- and pentacyclic heterocyclic compounds were obtained. The biologically studied compounds exhibited protection against PTZ seizures as well as some psychotropic effects. The biological assays evidenced that 13 of the 16 studied compounds showed a high anticonvulsant activity by antagonism with PTZ. The toxicity of the compounds was low. According to the results of the study of psychotropic activity, it was found that the selected compounds have a sedative effect, except compound 13, which exhibited activating behavior and antianxiety effects (especially compound 13). The studied compounds exhibited antidepressant effects, especially compound 13, which is similar to diazepam. Histopathological examination showed that compound 13 produced moderate changes in the brain and exhibited neuroprotective effects in the entorhinal cortex against PTZ-induced damage, reducing gliosis and neuronal loss. Docking studies revealed that out of 16 compounds, 3 compounds bound to the γ-aminobutyric acid type A (GABAA) receptor. Thus, the selected compounds demonstrated anticonvulsant, sedative, and activating behavior, and at the same time exhibited antianxiety and antidepressant effects. Compound 13 bound to the GABAA receptor and exhibited antianxiety, antidepressant, and neuroprotective effects in the entorhinal cortex against PTZ-induced changes.